Metastasis of cardiac rhabdomyosarcoma at lumbar spine: case report - Hongsaprabhas, MD, Chindanai; Yingsakmongkol, MD, Wicharn; Yuktanandana, MD, Pongsak (Journal of Southeast Asian Orthopaedics, 2022)
We report a case and review literatures of a 78-year-old man presenting with progressive dyspnea for 1 month. A diagnosis of cardiac pleomorphic rhabdomyosarcoma with lung and scalp metastasis was made then surgical tumor removal was performed. One month later the patient complained of severe low back pain. After complete investigation, he was diagnosed with metastatic rhabdomyosarcoma at lumbar spine and adjacent paravertebral soft-tissue. He underwent a second operation resulting in a satisfactory early postoperative outcome. He passed away approximately 6 weeks later as a result of severe congestive heart failure and irreversible respiratory failure. This is the first case report of metastatic cardiac pleomorphic rhabdomyosarcoma at lumbar spine which is assumed to be a rare and aggressive disease.